PENGARUH PUTARAN PENCACAH TERHADAP KAPASITAS CACAHAN RUMPUT GAJAH - Muhamad Agung Prasetyo; Catur Pramono; Xander Salahudin (Wahana Ilmuwan, 2017)
Along with a rapid the technological progress in the field of agriculture, enable farmers to be more in developing the technology, expecially in the field of cultivation farms. One of livestock reared a beef cattle. The cous that many main tarned the come frome a mating needles, such as diamond limousind, barman cross, boss taurus, and fries Holland. In addition, the maintenance requires less time than with other types of cow, but needs more feed. The breeds are Magelang in chop the gress is still use crescent moon that takes time and energy more. Therefore, breeder need aids in the process of chopped grass in order to save time and energy is sued. The purpose the chopped grass fodder know this is the capacity of the chopeed bulrush and find out a picture of bulrush results chop. The results here obtained in the from of the capacity of the chopped bulrush with the speed of turn chop 600 rpm, 700 rpm, 840 rpm and found the results obtained respectively for 18,36 kg/hr, 25,20 kg/h, and 55,72 kg/hour. It is visually results chop bulrush results chop using the speed loop of chopped 840 rpm shows the size of less than 1cm and the size of more than 1cm.